Association of PRPS1 Mutations with Disease Phenotypes. (24th May 2015) - Mittal, Rahul; Patel, Kunal; Mittal, Jeenu; Chan, Brandon; Yan, Denise; Grati, M'hamed; Liu, Xue Zhong
Abstract : Phosphoribosylpyrophosphate synthetase 1 ( PRPS1 ) codes for PRS-I enzyme that catalyzes the first step of nucleotide synthesis. PRPS1 gene mutations have been implicated in a number of human diseases. Recently, new mutations in PRPS1 have been identified that have been associated with novel phenotypes like diabetes insipidus expanding the spectrum of PRPS1 -related diseases. The purpose of this review is to evaluate current literature on PRPS1 -related syndromes and summarize potential therapies. The overexpression of PRPS1 results in PRS-I superactivity resulting in purine overproduction. Patients with PRS-I superactivity demonstrate uric acid overproduction, hypotonia, ataxia, neurodevelopment abnormalities, and postlingual hearing impairment. On the other hand, decreased activity leads to X-linked nonsyndromic sensorineural deafness (DFNX-2), Charcot-Marie-Tooth disease-5 (CMTX5), and Arts syndrome depending on the residual activity of PRS-I. Mild PRS-I deficiency (DFNX-2) results in non-syndromic progressive hearing loss whereas moderate PRS-I deficiency (CMTX5) and severe PRS-I deficiency (Arts syndrome) present with peripheral or optic neuropathy, prelingual progressive sensorineural hearing loss, and central nervous system impairment. Currently, purine replacement via S-adenosylmethionine (SAM) supplementation in patients with Arts syndrome appears to improve their condition. This suggests that SAM supplementation can alleviate symptoms of PRPS1 deficient patients and open new avenues of therapeutic intervention.